KOMPILASI HUKUM ISLAM SEBAGAI HUKUM TERAPAN BAGI HAKIM PENGADILAN AGAMA - Muhammad Gazali Rahman (IAIN Ambon, 2017)
Material law with regard to cases that the authority of Islamic Court before 1991, scattered in various books fiqhi that mejemuk. The plurality of this law, an obstacle to be a reference in the process of formulating the termination of the court. Birth of Presidential Decree No. 1 of 1991 on the Compilation of Islamic Law, as a matter of law in resolving the religious judge Religious Court case very effective. It is evident, with berdisparitasnya no longer any verdict in the same case. Applicability Compilation of Islamic Law as a legal matter in the Religious Court means the implementation and application of the Islamic law, is no longer directed by the will of its adherents, but a designated set of ranks of rulers and state institutions as regulatory authorities, and executive implementation, in particular related to the field of marriage, inheritance, perwakafan which has become a rule of civil law and public official. Keywords: compilation of Islamic law, judges, religious courts